2008
DOI: 10.1080/10715760802566574
|View full text |Cite
|
Sign up to set email alerts
|

Ceruloplasmin and myeloperoxidase in complex affect the enzymatic properties of each other

Abstract: Ceruloplasmin (CP), the multicopper oxidase of plasma, interacts with myeloperoxidase (MPO), an enzyme of leukocytes, and inhibits its peroxidase and chlorinating activity. Studies on the enzymatic properties shows that CP behaves as a competitive inhibitor impeding the binding of aromatic substrates to the active centre of MPO. The contact between CP and MPO probably entails conformational changes close to the p-phenylenediamine binding site in CP, which explains the observed activation by MPO of the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 38 publications
4
38
0
5
Order By: Relevance
“…Ceruloplasmin was also shown to inhibit the peroxidase activity of myeloperoxidase (20,22), but there were inconsistencies in the extent of inhibition, with values for inhibition ranging from 40 to 70%. The degree of inhibition also increased with increasing size of the peroxidase substrate (25). This suggested that binding of ceruloplasmin to myeloperoxidase hinders large substrates from accessing the active site of the enzyme.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Ceruloplasmin was also shown to inhibit the peroxidase activity of myeloperoxidase (20,22), but there were inconsistencies in the extent of inhibition, with values for inhibition ranging from 40 to 70%. The degree of inhibition also increased with increasing size of the peroxidase substrate (25). This suggested that binding of ceruloplasmin to myeloperoxidase hinders large substrates from accessing the active site of the enzyme.…”
mentioning
confidence: 71%
“…In subsequent studies, it was found to be a modest inhibitor of the halogenation activity of myeloperoxidase (24,25). Ceruloplasmin was also shown to inhibit the peroxidase activity of myeloperoxidase (20,22), but there were inconsistencies in the extent of inhibition, with values for inhibition ranging from 40 to 70%.…”
mentioning
confidence: 99%
“…There are many amino acid residues involved in interactions with fullerene C 60 on ceruloplasmin surface, which are considered as crucial for ceruloplasmin-lactoferrin or ceruloplasmin-myeloperoxidaze complexes (see Table 1). Around fragments Arg883-Arg892, His667-Trp669, and Cys699-Leu710 which are probably involved in interactions of cerruloplasmin with myeloperoxidaze [39,64,65] we found about 3, 10, and 8% populations of docked C 60 . Also, His1028-Val1037 fragment, previously recognized as important for binding various proteins to ceruloplasmin surface [66], was involved in interactions with fullerene molecules.…”
Section: Binding Sites Analysismentioning
confidence: 97%
“…Fagments Arg883-Arg892 [64], His667-Trp669 [65] and loop Cys699-Leu710 [39] are probably involved in interactions of cerruloplasmin with myeloperoxidaze.…”
Section: Methodsmentioning
confidence: 99%
“…In halogenating or oxidative stress, the low level of CP is associated with the disturbance of its ability to form complexes with MPO and inhibit both the chlorinating and peroxide activity of the enzyme. [23,24] The low concentration of VitE found in asthma patients has an unfavorable prognostic effect on the treatment of the disease. VitE is able to regulate the biotransformation and pharmacological effect of drugs by changing the activity of xenobiotic-metabolizing enzymes, including the system of cytochrome Р450.…”
Section: Discussionmentioning
confidence: 99%